INVENTARISASI POTENSI OBYEK DAYA TARIK WISATA DAN PERSEPSI MASYARAKAT DI DESA KIRAM KABUPATEN BANJAR - M Yunus Agisna Iswan; Abdi Fithria; Mufidah Asy'ari (Universitas Lambung Mangkurat, 2020)
The purpose of this study to inventory potential tourist attraction objects and map them. Assessing community perceptions in developing tourist attraction objects. In this study using the method of observation, interviews or questionnaires, documentation, analyzing data using Geographic Information Systems (GIS) and tabulating data that produced research results in the form of Kiram Village Tourism Object map and community perceptions of Kiram Village on the development of Tourism Attractions in the village of Kiram. Results of Inventory of Tourist Attraction Objects in Kiram Village There are 7 Tourism Objects, namely: Kiram Park, Community Plantation, Gunung Mawar, Mount Pamaton, Animal Husbandry Honey Bee, ULM Dam, and Bamboo Rafting. The results of the community perception in the development of the Tourist Attraction Object in Kiram Village were strongly agreed (50%) and agreed (50%).Keyword : Kiram Village, Inventory of Tourist Attraction Objects, Community Perception, Development of Tourist Attraction Objects